TB500/TB1000 and SGF1000: A scientific approach for a better understanding of misbranded and adulterated drugs. Issue 4 (23rd December 2022) - Delcourt, Vivian; Garcia, Patrice; Chabot, Benjamin; Barnabé, Agnès; Bouscarel, Maëlle; Loup, Benoit; Popot, Marie‐Agnès; Bailly‐Chouriberry, Ludovic
Abstract: Nowadays, numerous websites attempt to commercialize over the internet various products, regardless of the lack of approval by the EMA or the FDA either for human or veterinary use. These products are often produced after aborted drug development due to insufficient or deleterious biological effects, synthesized based on natural products, or only based on scientific literature. However, the administration of such products is dangerous, considering the lack of official control over the production of these substances and the absence of approval by health authorities. In this short communication, we provide an extensive analysis of three misbranded and adulterated products sold over the internet named TB500, TB1000, and SGF1000. We confirm that the content of TB500/TB1000 products is not systematically consistent with it's former descriptions, but also that SGF1000 is mainly composed of sheep extracellular matrix (ECM) and blood proteins, and the signal corresponding to the purported growth promoters is excessively diluted. Abstract : Numerous websites commercialize misbranded and adulterated drugs including but not limited to TB500/TB1000 and SGF1000 despite the lack of proven efficacy or approval by health authorities. In this short communication, we provide an extensive analysis of TB500, TB1000, and SGF1000 and highlight important inconsistencies regarding their contents.